COVID-19: Aspects of genetic susceptibility and congenital defects - Estela Morales Peralta; Miguel Alfonso Alvarez Fornaris (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: COVID-19 (acronym for Coronavirus Disease 2019) is a recently described infectious disease caused by SARS-CoV-2, without effective treatment. Identification of genetic variants involved in the response to COVID-19 as well as the possibility of maternal-fetal transmission of SARS-CoV-2 will not only allow us to expand our knowledge of the pathophysiology of COVID-19, but also stratify population groups according to their risks in order to implement preventive measures and personalized treatments, including the priority in the use of vaccines. Objective: To describe aspects related to congenital defects and genetic susceptibility to the SARS-CoV-2 virus. Material and Methods: A bibliographic review was carried out. Medline and PubMed bibliographic databases were searched.  Studies published between 2019 and 2020 were included as well the ones recommended by experts, preferably published within the last 10 years. After qualitative evaluation, synthesis was made. Development: Mutations in ACE2, ACE1, TMPRSS2, TLR7 genes, as well as HLA haplotypes associated with genetic susceptibility to COVID-19 are described. Variants in the genes SLC6A20, LZTFL1, CCR9, FYCO1, CXCR6, XCR1 and in those codifying Vitamin D receptor and proinflammatory cytokines (IL-1, IL-6, IL-12, IFN-γ, and TNF-α) could be related to an increased susceptibility to SARS-CoV-2. Due to the risk of vertical transmission of COVID-19 and its possible teratogenic effect, pregnant women are included in the risk group. Conclusion: Human genetic variants are factors of genetic susceptibility to the SARS-CoV-2 virus which may cause congenital defects.